Victor Herbert : A Theatrical Life - Gould, Neil, 1943- (Book collections on Project MUSE., 2008)
Victor Herbert is one of the giants of American culture. As a musician, conductor, and, above all, composer, he touched every corner of American musical life at the turn of the century, writing scores of songs, marches, concerti, and other works. But his most enduring legacy is on a different kind of stage, as one of the grandfathers of the modern musical theater. Now, Victor Herbert has the biography he deserves. Neil Gould draws on his own experience as a director, producer, and scholar to craft the first comprehensive portrait in fifty years of the Irish immigrant whose extraordinary talents.